Climate change and its impact on food and nutrition insecurity : a case of the Northwest region of Bangladesh - Roy, Debashis; Datta, Avishek; Anal, Anil Kumar; Kuwornu, John K. M.; Center for Development Innovation, Wageningen UR, The Netherlands (Pathum Thani, Thailand : Asian Institute of Technology, 2017)
Climate change is an issue of global concern and it is a growing evidence that Bangladesh faces a lot of negative impacts throughout the country. It impels negative impacts on different development sectors through a variety of ways and it is presumed that food and nutrition security could be affected negatively through climate change events. Although several studies have been conducted on climate change issue in Bangladesh, most of them were focused in the southern regions of Bangladesh. Thus, the present study was carried out in the northwest region of Bangladesh focusing on climate change impacts on food and nutrition insecurity of the smallholder households. A total of 252 smallholder households were interviewed during November 2016 to January 2017 to assess their perception to climate change, household food insecurity access and dietary diversity for women of reproductive age (15-49 years). The Household Food Insecurity Access scale was used to explore food insecurity status and on the other hand, the Minimum Dietary Diversity for Women of reproductive age scale was used to find out dietary diversity during last 24 hours. Smallholder farmers{u2019} perception to climate change were then compared with the meteorological trends during 1986 to 2015 period. The major findings revealed that farmers{u2019} perception to climate change were coherent with the meteorological trends, and temperature parameters were perceived as increased, while, rainfall parameters were perceived as decreased. Majority of the households perceived that climate change had high impacts on crop production in the study areas. Household food insecurity indicator revealed that more than half of the households were mildly food insecure and food secure households were greater in Kurigram district compared with Nilphamari district. Overall food insecurity index pointed out that food insecurity access was higher in Nilphamari district than Kurigram district. The findings also revealed that more than half of the women of reproduction age had low dietary diversity and it was slightly critical in Nilphamari district compared with Kurigram district. Adaptation measures to minimize climate change impacts by the households were medium in Kurigram district, while, low adaptation was recorded in Nilphamari district. Almost all of the households were found to practice compost and manure application in the fields and heat tolerant rice variety was the least practiced adaptation measure in the study areas. However, providing emphasis on climate change mitigation and adaptation along with policy consideration, food and nutrition insecurity could be lessened.
A Thesis submitted in partial fulfillment of the requirements for the degree of Master of Science in Agricultural Systems and Engineering
Thesis (M.Sc.) - Asian Institute of Technology, 2017
Keywords: Food security -- Bangladesh; Climatic changes -- Bangladesh; Nutrition -- Bangladesh